A preparation method and application of carbonate mineralized collagen scaffold material

By using carbonate and bicarbonate treatment in collagen gel and introducing metal cations, the formation of insoluble carbonate deposits in collagen fibers is solved, and the problem of poor biodegradability and osteogenic performance of traditional mineralized collagen stents is achieved, and higher mechanical strength and biodegradability are achieved, thereby promoting bone repair.

CN116510088BActive Publication Date: 2025-04-29ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310494884.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-05
Publication Date
2025-04-29
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

Traditional mineralized collagen stents have problems with poor biodegradability and osteogenic performance, which limits their clinical application.

Method used

The collagen gel is treated by using reagent A, composed of carbonate and bicarbonate, and reagent B, composed of polynegative electrolyte-metal cation complex, so that carbonate or bicarbonate ions can enter the collagen fibers and attract metal cations to deposit in an orderly manner in the collagen fibers.

Benefits of technology

It improves the mechanical strength and biodegradability of the material, slowly releases functional metal cations, promotes osteogenesis, and enhances the success rate of bone defect repair and bone grafting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116510088B_ABST
    Figure CN116510088B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a carbonate mineralized collagen scaffold material. The preparation method is to first immerse the collagen gel in reagent A, the reaction temperature is 25-37°C, the reaction time is 1-24 hours, and after the reaction is completed, the excess A liquid on the surface of the collagen gel is removed, and the collagen gel is mixed with reagent B for reaction, the reaction temperature is 25-37°C, and the collagen gel is taken out and thoroughly rinsed, and dried to obtain a carbonate mineralized collagen scaffold material. Reagent A is a soluble carbonate and bicarbonate solution with a pH of 9.5-10, and reagent B is a polyelectrolyte-metal cation suspension. The carbonate mineralized collagen scaffold material prepared by this method has a structure in which the inside and outside of the collagen fiber are mineralized simultaneously, and has good biocompatibility and degradability, and slowly and continuously releases functional metal cations by forming insoluble carbonates in collagen to promote bone defect repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomaterials, and in particular relates to a preparation method and application of a carbonate mineralized collagen scaffold material. Background Art

[0002] Traumatic fractures, bone infection debridement, osteoporotic fractures and bone tumor resection have caused bone defects to become a common clinical problem, bringing great pressure to the medical system. At present, the treatment methods for bone defects mainly include autologous bone, allogeneic bone and artificial bone transplantation. However, autologous bone transplantation is limited by the donor area, and allogeneic bone / xenogeneic bone transplantation and artificial bone transplantation are prone to cause severe immune rejection reactions in the recipient. Artificially synthesized bone substitute materials such as scaffold materials, tissue engineering bones composed of growth factors and seed cells, 3D printed bone substitute scaffolds and hydrogels have also been widely used. However, tissue engineering bone has problems such as high cost, biosafety and local bone absorption, while 3D printed bone substitute materials have problems such as low level of bone tissue structure simulation and inability to effectively establish early vascular access. Collagen-based bone substitute materials prepared by mineralization methods can effectively reduce costs and simulate natural bone tissue structure. Hydroxyapatite (HAp), as the inorganic substance with the highest content in human bones, is the most commonly used mineral in biomimetic mineralized collagen scaffolds. However, HAp has the defects of being difficult to degrade and its degradation is uncontrollable, which limits its clinical application as a bone repair material.

[0003] The mineralization mode of mineralized collagen material mainly includes extra-fiber mineralization and intra-fiber mineralization. The preparation method of extra-fiber mineralized collagen material is to simply mix minerals and collagen, and the obtained collagen material has limited mechanical strength, and there are problems such as too fast ion release and low biocompatibility. Intra-fiber mineralization can effectively simulate the multi-level structure of bone tissue, also known as biomimetic mineralization. The biomimetic mineralized collagen material has strong mechanical properties, slow ion release and good biocompatibility. The preparation method of biomimetic mineralized collagen material is usually to react amorphous minerals with polyelectrolyte stability with collagen fibers, but there are problems such as long reaction time and low mineralization efficiency. Patent CN110693724B describes that collagen is treated successively with reagent A containing polyelectrolyte-calcium complex and calcium ions and reagent B containing phosphate, which can quickly achieve intra-collagen mineralization. However, the biodegradability and bioabsorbability of the mineralized collagen scaffold obtained by this method are limited. Calcium carbonate, strontium carbonate and magnesium carbonate have good biocompatibility. The calcium ions, strontium ions and magnesium ions released by crystal dissolution have an osteogenic effect, and strontium ions also have an anti-inflammatory effect. All three carbonates can make up for the defects of HAp in biodegradability and bioabsorbability. The mineralized collagen scaffold material deposited in the collagen fibers of calcium carbonate, strontium carbonate and magnesium carbonate prepared by the biomimetic mineralization method is an ideal bone defect repair or bone transplant material with broad clinical application prospects. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of poor biodegradability and osteogenic performance of traditional mineralized collagen scaffolds, and to provide a preparation method and application of a carbonate mineralized collagen scaffold material.

[0005] The invention provides a method for preparing a carbonate mineralized collagen scaffold material. The method comprises the following steps: firstly immersing a collagen gel in a reagent A for reaction at a temperature of 25 to 37° C., drying the surface of the gel after the reaction, and then reacting the collagen gel with a reagent B at a temperature of 25 to 37° C., taking the gel out, rinsing and drying the gel to obtain the carbonate mineralized collagen scaffold material.

[0006] The reagent A comprises at least one carbonate and at least one bicarbonate; the carbonate is selected from sodium carbonate and potassium carbonate; the bicarbonate is selected from sodium bicarbonate and potassium bicarbonate; preferably, sodium carbonate and sodium bicarbonate solutions are used.

[0007] The reagent B is a suspension containing a polynegative electrolyte and a metal cation; the metal cation is one or more of calcium ions, strontium ions or magnesium ions.

[0008] Preferably, the metal cation is added in the form of a soluble salt, for example, chloride and / or its hydrate, nitrate and / or its hydrate, fluoride and / or its hydrate, acetate and / or its hydrate related to the metal cation. Chloride and its hydrate, and nitrate and its hydrate are preferably used because they have higher solubility.

[0009] Preferably, the metal cations used are calcium ions, strontium ions and magnesium ions, which have good osteogenic properties.

[0010] Preferably, the dosage volume ratio of the reagent A to the reagent B is 1:(0.1-10), preferably 1:1. Preferably, the molar ratio of the total concentration of carbonate ions and bicarbonate ions in the reagent A to the total concentration of metal cations in the reagent B is (0.1-10):1; preferably (1-2):1; the reagent A and the reagent B are stored separately.

[0011] Preferably, the ion concentration ratio of carbonate and bicarbonate in the reagent A is 1:(1-10), preferably 1:(3-4); preferably, the total ion concentration of carbonate and bicarbonate in the reagent A is 1-4 mol / L, preferably 1.5 mol / L.

[0012] Preferably, the content of the polyanionic electrolyte in the reagent B is 0.5-10 g / L, preferably 2-4 g / L, and its average molecular weight is 1-15 kDa, preferably 6-8 kDa; preferably, the polyanionic electrolyte is one or more of polyaspartic acid, polyacrylic acid, polyglutamic acid, polyvinylphosphonic acid and carboxymethyl chitosan, preferably polyaspartic acid, because it has strong cationic chelating ability and good biocompatibility; preferably, the concentration of the metal cation is 0.5-10 mol / L, preferably 2.5-5.5 mol / L.

[0013] Preferably, the metal cation in the reagent B is added in the form of soluble chloride, soluble hydrated chloride, soluble nitrate or soluble hydrated nitrate. Among them, the metal cation is preferably calcium ion, strontium ion and magnesium ion, each of which is added in the form of calcium chloride dihydrate, strontium chloride hexahydrate and magnesium chloride hexahydrate, respectively, and reacts with the reagent A in the collagen fiber to preferably form calcium carbonate, strontium carbonate and magnesium carbonate crystals.

[0014] Preferably, the solvent of the reagent A and the reagent B is deionized water or PBS buffer, preferably deionized water; the pH value of the reagent A and the reagent B is 9.5-10.

[0015] Preferably, the reaction time of the collagen gel and reagent A is 1 to 24 hours, and the reaction time of the collagen gel and reagent B is 1 to 24 hours. The reaction time of the collagen gel and reagent A is preferably 6 hours, and the reaction time with reagent B is preferably 2 to 4 hours. Preferably, the reaction temperature of the collagen gel and reagent A and reagent B is 25 to 37°C, preferably 37°C.

[0016] Preferably, the collagen gel is made of one or more of natural unmineralized collagen, recombinant type I collagen from animal sources such as rat tail collagen, bovine Achilles tendon collagen and fish skin collagen, demineralized dentin collagen, demineralized bone collagen and artificial collagen fibers, preferably recombinant type I rat tail collagen and bovine Achilles tendon collagen.

[0017] Preferably, the mineralized collagen gel needs to be dried to obtain the mineralized collagen scaffold material; the drying method includes freeze drying, gradient dehydration drying with ethanol and hexamethyldisilazane (HMDS), vacuum drying, oven drying and air drying, preferably freeze drying.

[0018] The carbonate mineralized collagen scaffold material obtained by the present invention can be used for repairing bone defects or bone transplantation, such as for preparing biological repair materials for bone defects or bone transplantation, and can be directly used as filling materials for bone defects or bone transplantation.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The carbonate mineralized collagen scaffold material in the present invention is different from the collagen material prepared by simply physically mixing minerals and collagen. The collagen gel is treated with reagent A composed of carbonate and bicarbonate, and reagent B composed of a mixture of a polynegative electrolyte-metal cation complex and a metal cation, so that carbonate or bicarbonate ions enter the collagen fiber, and then attract the polynegative electrolyte-metal cation complex and the metal cation, and the insoluble carbonate is deposited in the collagen fiber in an orderly manner, so as to achieve the purpose of increasing the mechanical strength of the material. The insoluble carbonate deposited in the collagen fiber can slowly release the functional metal cation to achieve the purpose of promoting osteogenesis. Compared with the traditional hydroxyapatite-based collagen material, the insoluble carbonate introduced into the collagen fiber not only retains good biocompatibility, but also has ideal biodegradability and bioabsorbability, and can effectively improve the success rate of bone defect repair and bone transplantation.

[0021] The carbonate mineralized collagen scaffold material of the present invention will be an osteogenic collagen material with excellent clinical effect, capable of rapidly inducing new bone formation, and effectively being absorbed or degraded by tissues, and having broad application prospects in bone defect repair and bone transplantation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Transmission electron microscopy image of mineralized collagen of calcium carbonate in fibers prepared by the method of Example 1; scale bar: 200 nm;

[0023] Figure 2 This is a transmission electron micrograph of mineralized collagen with strontium carbonate in fibers prepared using the method of Example 2. Scale bar: 200 nm.

[0024] Figure 3 This is a transmission electron micrograph of mineralized collagen with magnesium carbonate in fibers prepared using the method of Example 3. Scale bar: 200 nm. DETAILED DESCRIPTION

[0025] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0026] Implementation Case 1

[0027] Weigh 3.59 g of sodium carbonate, 3.6 g of sodium bicarbonate and 50 g of deionized water by weight. The preparation method is: first dissolve sodium carbonate in 10 g of deionized water, then dissolve sodium bicarbonate in 40 g of deionized water, and finally mix the sodium carbonate and sodium bicarbonate solutions to obtain reagent A.

[0028] Weigh by weight percentage: 20g of calcium chloride dihydrate, 0.1g of polyaspartic acid (average molecular weight of 6-8kDa) and 10g of deionized water. The preparation method is: first dissolve the polyaspartic acid in deionized water, then add calcium chloride dihydrate, stir and adjust the pH to 9.5 with 10mol / L sodium hydroxide solution to obtain reagent B.

[0029] Take 300 μL rat tail collagen stock solution (3 mg / mL) and incubate in an ammonia environment for 4 hours, then rinse in deionized water 3 times, stand at room temperature for 24 hours, cross-link with 0.1wt% glutaraldehyde for 2 hours to obtain recombinant collagen gel. The collagen gel is soaked in reagent A for 6 hours, taken out and the surface is blotted dry, then soaked in reagent B for 2 hours, taken out and rinsed with deionized water to obtain mineralized collagen gel with calcium carbonate in the fiber. The mineralized collagen gel is placed in an environment of -80°C for 12 hours, and then freeze-dried for 24 hours to obtain a mineralized collagen scaffold material with calcium carbonate deposited in the collagen fiber. The deposition of calcium carbonate in the collagen fiber can slowly release calcium ions to promote osteogenesis. Figure 1 This is a transmission electron micrograph of mineralized collagen fibers of intra-fiber calcium carbonate prepared by the method of Example 1, which shows that calcium carbonate crystals are deposited in collagen fibers, which is different from the extra-fiber calcium carbonate mineralized collagen material obtained by simple physical mixing of common calcium carbonate particles and collagen fibers. The intra-fiber mineralized collagen scaffold of calcium carbonate obtained by the present invention has a good calcium ion sustained release effect. The calcium ion release amount of the scaffold after soaking in 15 mL PBS solution for 1, 3, 5, 7, 14 and 28 days can reach 16.87±3.26ppm, 12.87±1.37ppm, 12.22±0.92ppm, 8.04±0.87ppm, 4.32±1.14ppm and 5.06±2.26ppm, respectively, which can promote osteogenesis while maintaining good biocompatibility.

[0030] Implementation Case 2

[0031] The preparation method of reagent A and the preparation method of collagen gel are the same as those in Example 1.

[0032] Weigh 11 g of strontium chloride hexahydrate, 0.03 g of polyaspartic acid (average molecular weight 6-8 kDa) and 10 g of deionized water by weight percentage. The preparation method is as follows: first dissolve the polyaspartic acid in deionized water, then add strontium chloride hexahydrate, stir, and adjust the pH to 9.5 with 1 mol / L sodium hydroxide to obtain reagent B. The preparation process of mineralized collagen gel in strontium carbonate fiber is the same as that of implementation case 1, except that the immersion time in reagent B is extended to 4 hours. Figure 2The transmission electron microscope image of the mineralized collagen fiber with strontium carbonate in the fiber prepared by the method of Example 2 shows the deposition of strontium carbonate crystals in the collagen fiber. This is different from the extra-fiber strontium carbonate mineralized collagen material obtained by simply physically mixing strontium carbonate particles and collagen fibers. The strontium carbonate mineralized collagen scaffold in the fiber obtained by the present invention has a better strontium ion sustained release effect, thereby achieving the purpose of promoting osteogenesis and anti-inflammation.

[0033] Implementation Case 3

[0034] The preparation method of reagent A and the preparation method of collagen gel are the same as those in Example 1.

[0035] Weigh 13 g of magnesium chloride hexahydrate, 0.1 g of polyaspartic acid (average molecular weight of 6-8 kDa) and 10 g of deionized water by weight percentage. The preparation method is as follows: first dissolve polyaspartic acid in deionized water, then add magnesium chloride hexahydrate, stir, and adjust the pH to 9.5 with 5 mol / L sodium hydroxide to obtain reagent B. The preparation process of mineralized collagen gel in magnesium carbonate fiber is the same as that of implementation case 1 except that the immersion time in reagent B is extended to 4 hours. Figure 3 The transmission electron micrograph of the mineralized collagen fiber with magnesium carbonate in the fiber prepared by the method of Example 3 shows the deposition of magnesium carbonate crystals in the collagen fiber. This is different from the extra-fiber magnesium carbonate mineralized collagen material obtained by simply physically mixing magnesium carbonate particles and collagen fibers. The mineralized collagen scaffold in the magnesium carbonate fiber obtained by the present invention has a better magnesium ion sustained release effect, thereby achieving the purpose of promoting osteogenesis.

[0036] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing a carbonate mineralized collagen scaffold material, characterized in that: First, immerse the collagen gel in reagent A for reaction at a temperature of 25 to 37° C. After the reaction is completed, dry the surface of the gel, and then react the collagen gel with reagent B at a temperature of 25 to 37° C. After taking out, rinse and dry, and obtain a carbonate-based mineralized collagen scaffold material; The reagent A comprises at least one carbonate and at least one bicarbonate; the carbonate is selected from sodium carbonate and potassium carbonate; the bicarbonate is selected from sodium bicarbonate and potassium bicarbonate; the ion concentration ratio of the carbonate and bicarbonate is 1:(1-10), the total concentration of the carbonate and bicarbonate is 1-4 mol / L, and the pH is 9.5-10; the reagent B is a suspension comprising a polynegative electrolyte and a metal cation; the metal cation is one or more of calcium ions, strontium ions or magnesium ions; the metal cation is added in the form of one or more of soluble chloride, soluble hydrated chloride, soluble nitrate or soluble hydrated nitrate.

2. The method for preparing the carbonate mineralized collagen scaffold material according to claim 1, characterized in that: The dosage volume ratio of the reagent A and the reagent B is 1:(0.1-10); the molar ratio of the total concentration of metal cations in the reagent B to the total concentration of carbonate ions and bicarbonate ions in the reagent A is (0.1-10):1; the reagent A and the reagent B are stored separately.

3. The method for preparing the carbonate mineralized collagen scaffold material according to claim 1, characterized in that: The content of the polyanionic electrolyte used in the reagent B is 0.5-10 g / L, and its average molecular weight is 1-15 kDa. The polyanionic electrolyte is one or more of polyaspartic acid, polyacrylic acid, polyglutamic acid, polyvinylphosphonic acid and carboxymethyl chitosan; the concentration of the metal cation is 0.5-10 mol / L, and the pH is 9.5-10.

4. The method for preparing the carbonate mineralized collagen scaffold material according to claim 1, characterized in that: The solvents of the reagent A and the reagent B are deionized water or PBS buffer.

5. The method for preparing the carbonate mineralized collagen scaffold material according to claim 1, characterized in that: The mixing reaction time of the collagen gel and reagent A is 1 to 24 hours, and the mixing reaction time of the collagen gel treated with reagent A and reagent B is 1 to 24 hours.

6. The method for preparing the carbonate mineralized collagen scaffold material according to claim 1, characterized in that: The collagen gel is made of natural unmineralized collagen, recombinant type I collagen from animal sources, demineralized dentin collagen, demineralized bone collagen or artificial collagen fiber.

7. The carbonate mineralized collagen scaffold material prepared by the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • A tooth mineralizing solution and its mineralization method

    CN110693724B

  • Preparation method and application of anti-inflammatory osteogenesis-promoting mineralized collagen material

    CN114470332A